2018
DOI: 10.1590/1414-431x20187564
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic receptor β3 is involved in the memory consolidation process in mice

Abstract: Attention and emotion have a positive impact on memory formation, which is related to the activation of the noradrenergic system in the brain. The hippocampus and amygdala are fundamental structures in memory acquisition, which is modulated by noradrenaline through the noradrenergic receptors. Pharmacological studies suggest that memory acquisition depends on the action of both the β3 (β3-AR) and β2 (β2-AR) receptor subtypes. However, the use of animal models with specific knockout for the β3-AR receptor only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
3
7
0
Order By: Relevance
“…WT mice spent significantly more time with the new object, 3h (O2) (p<0.0001; t=5.06) and 24 h (O3) (p<0.0001; t=8.52) after the familiarization period(Figures 3 A-B). In contrast, the Adrβ3KO spent similar amounts of time with old (O1) and new objects (O2) 3 h (p=0.62; t=1.03) and 24h (O3) (p=0.1; t=2.06) after the familiarization period(Figure 3 A-B), confirming data from a previous study(13) showing that the absence of Adrβ3 impairs memory consolidation. Remarkably, EE was effective in correcting the memory impairment displayed by the Adrβ3KO mice both 3h (O2) (p<0.0001; t=8.06) and 24 h (O3) (p=0.0014; t=3.73) after the familiarization period(Figure 3 C-D).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…WT mice spent significantly more time with the new object, 3h (O2) (p<0.0001; t=5.06) and 24 h (O3) (p<0.0001; t=8.52) after the familiarization period(Figures 3 A-B). In contrast, the Adrβ3KO spent similar amounts of time with old (O1) and new objects (O2) 3 h (p=0.62; t=1.03) and 24h (O3) (p=0.1; t=2.06) after the familiarization period(Figure 3 A-B), confirming data from a previous study(13) showing that the absence of Adrβ3 impairs memory consolidation. Remarkably, EE was effective in correcting the memory impairment displayed by the Adrβ3KO mice both 3h (O2) (p<0.0001; t=8.06) and 24 h (O3) (p=0.0014; t=3.73) after the familiarization period(Figure 3 C-D).…”
supporting
confidence: 88%
“…Isopropoterenol, an agonist for Adrβ1 and Adrβ2, increases neural plasticity in the CA1 and CA3 regions and in the dentate gyrus in the hippocampus, while propranolol, a Adrβ1 and Adrβ2 antagonist, blocks LTP in the CA1 region and the dentate gyrus (9)(10)(11)(12). In addition, the absence of the Adrβ3 receptor induces important deficits in the formation of short-and long-term memory (13).…”
Section: Introductionmentioning
confidence: 99%
“…Gibbs et al showed that memory formation at the time of learning is enhanced by the administration of β 3 -AR agonist CL316243 to day-old chicks, a process most likely due to an increase in glucose uptake via GLUT3 [163]. Interestingly, β 3 -AR KO mice show a decrease in mRNA level of GLUT3 transporter in the amygdala and impairments in long- and short-term memory formation [164].…”
Section: β3-ar As Therapeutic Targetmentioning
confidence: 99%
“…This also drives neuronal activity in the locus coeruleus (the main point from which 2 noradrenergic neurons project throughout the brain), and is partially blocked by inhibition of Adrβs [7,8]. Although the role of Adrβ1 and Adrβ2 is well established, a recent increase in experimental evidence has been bringing light to the role of Adrβ 3 as a key role in mediate memory consolidation in rodents [9,10]. Confirming its relevance, the administration of Adrβ3 agonist reversed the memory impairment of animal models for Alzheimer's disease [11].…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of astrocytic EAAT2, the major glutamate transporter in the brain, leads to early deficits in short-term memory and in spatial reference learning and longterm memory [18]. Considering that the inactivation of Adrβ3 induces a significant impairment in short-and long-term memory [10] and that the neuroinflammation controls it [19], we hypothesized that the use of MS could reverse the memory impairment exhibited by the Adrβ3 knock-out (Adrβ3KO) mice. The cognitive impairment exhibited by Adrβ3KO mice at 120 days of life was rescued when an 8-week program of MS was initiated after weaning at 21 days of life.…”
Section: Introductionmentioning
confidence: 99%